45 A simple questionnaire-based triage tool to identify patients potentially eligible for referral to an advanced heart failure centre. (30th September 2020) - Murphy, L; Giblin, G; Caples, N; Black, R; O'Neill, J; Halley, C; Mahon, N; McDonald, K; Joyce, E
Abstract : Introduction: Accurate prevalence data for advanced heart failure (HF), reported to range between 2–10% of the chronic HF population, are lacking. Determining the proportion of patients potentially suitable for referral to a specialist advanced HF center is crucial for accurate service planning and resource provision, particularly in the evolving era of durable mechanical circulatory support. Purpose: To identify the population of patients potentially eligible for referral for assessment for advanced surgical therapies to the National Advanced HF and Cardiac Transplant center, using a quick one-page prospective survey. Methods: A survey comprising 13 potential markers of advanced HF was developed, modified from the 2018 position statement of the Heart Failure Association of the European Society of Cardiology. This was distributed to 26 HF clinic centers nationally. Each center was asked to complete the survey on consecutive patients over a 3-month period who fulfilled the following three criteria: 1) age < 65 years; 2) ejection fraction (EF) < 40% and 3) HF of >3 months duration. Results: In all, 21 of 26 HF clinic centers participated in the survey. Across the period of inclusion, 4950 all-comer HF patients were seen in 21 centers. Of these, 375 fulfilled the inclusion criteria, comprising 279 (74.4%) males with a median age of 57 years. In total, 246 (66%) of the completed surveys had one or more potential markers for advanced HF, representing just under 5% of the total all-comer HF population seen across the same time period. Of these, 67 patients (27%) had at least two, 48 (20%) had three and 40 (16%) had ≥ 4 potential markers. The most frequently noted markers were ≥1 hospitalization or unscheduled clinic review (56%), intolerance to renin-angiotensin-aldosterone system inhibitors due to hypotension or renal dysfunction (29%) and intolerance to beta-blockers due to hypotension (27%). Almost one-quarter of patients reported NYHA Class III or IV symptoms (figure 1 ). Conclusions: In this index prospective National survey, approximately 5% of an all-comer routine HF clinic population and two-thirds of a pre-selected HF with reduced EF <65 years cohort, were found to have at least one clinical or biochemical marker suggesting advanced or impending advanced HF. Notably, almost one-quarter of patients in this chronic outpatient 'snapshot' population have advanced HF symptoms. This simple one-page triage tool may be useful to identify a population potentially eligible for referral to an advanced HF center for assessment for advanced surgical therapies, thereby aiding resource utilization and service planning.